CADASTRING THE RENEWABLE ENERGY SOURCES IN UZBEKISTAN - Alijonov Abbosbek; Sayfullayev Abdulaziz (Лучшие интеллектуальные исследования, 2024)
It is necessary to train competitive specialists with in-depth knowledge to carry out research, design, construction, operation, repair and reconstruction of energy facilities built on non-traditional and renewable energy sources. Taking this into account, we will consider the solar cadastre of solar energy, which is considered one of the renewable energy sources.